A high-entropy FeCoNiAlTi alloy with a lattice truss structure and its preparation method.
By using FeCoNiAlTi high-entropy alloy with dot matrix lattice truss structure, a porous structure with high energy absorption efficiency was prepared using selective laser melting technology, which solved the problem of low compressive strength and energy absorption efficiency of existing materials in the biomedical industry. Achieve high-performance lightweight energy-absorbing material.
Patent Information
- Application Number
- CN202410576653.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-10
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-05-10
AI Technical Summary
Existing metal porous materials have low compressive strength and energy absorption efficiency in medical implants in the biomedical industry and cannot meet demanding application requirements.
FeCoNiAlTi high-entropy alloy with dot matrix lattice truss structure was prepared by selective laser melting technology to prepare a porous structure with high energy absorption efficiency. The single-cell structure of this structure includes simple cubes, body-centered cubes or body-centered cube pillars. Through three-dimensional modeling and printing parameter optimization, a lattice structure with high microscopic density and excellent performance is achieved.
It achieves high compliance and energy absorption capacity, significantly improves the compressive strength and energy absorption efficiency of the material. It is suitable for vehicles, aerospace, biomedicine and other fields, providing lightweight energy absorption characteristics for buffering and protection.
Smart Images

Figure CN118404094B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloy rapid prototyping with designable structure, and in particular relates to a FeCoNiAlTi high entropy alloy with a lattice truss structure and a preparation method thereof. Background Art
[0002] With the rapid development of aerospace, machinery and medical fields, the demand for lightweight and high-performance engineering materials is also increasing. Existing traditional materials and structures can no longer meet the demand for lightweight in these fields. Additive manufacturing technology, as an emerging material forming technology, has the advantages of high degree of freedom and good processing and forming properties. Compared with traditional materials, porous materials produced by additive manufacturing technology have the advantages of light weight, impact resistance and high strength. Selective laser melting (SLM) is one of the most common additive manufacturing technologies used to manufacture metal lattice structures. It can produce high-quality metal parts that meet complex and specific purposes, and is very suitable for the production of customized metal parts. Metal lattice structure is a type of porous structure with a periodic lattice structure. Pillar-based lattice materials are the most common form of mechanical metamaterials. Mechanical metamaterials are usually composed of interconnected pillars, plates, shells or mixtures thereof, organized into repeated unit cells.
[0003] However, most of the lattice structures reported so far have the problem of insufficient strength, especially for medical implants in the biomedical industry with harsh service environments. The relative density of the common porous Ti-6Al-4V material manufactured by SLM is 10-30%, but the compressive strength and energy absorption efficiency are low. Similar biomimetic materials include AlSi12Mg, whose lattice skeleton structure has a compressive strength of less than 20MPa under similar relative density conditions. In order to solve problems such as low compressive strength or low specific modulus, some researchers have proposed a variety of models for the auxiliary design of lattice materials, such as the Gibson-Ashby model. However, due to the inherent limitations of material composition, it is urgent to develop new metal lattice materials with low density and high strength characteristics. Summary of the invention
[0004] In order to solve the above technical problems, the present invention proposes a FeCoNiAlTi high entropy alloy with a lattice truss structure and a preparation method thereof. The FeCoNiAlTi high entropy alloy with a lattice truss structure prepared by the preparation method provided by the present invention has high energy absorption efficiency.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a FeCoNiAlTi high entropy alloy with a lattice truss structure, comprising the following steps:
[0007] The FeCoNiAlTi high entropy alloy powder is subjected to selective laser melting to obtain a FeCoNiAlTi high entropy alloy with a lattice truss structure;
[0008] The unit cell structure of the lattice truss structure includes a simple cubic SC, a body-centered cubic BCC or a body-centered cubic strut BCCZ.
[0009] Preferably, the particle size of the FeCoNiAlTi high entropy alloy powder is 15 to 53 μm.
[0010] Preferably, the size of the unit cell structure is 2mm×2mm×2mm~10mm×10mm×10mm, the diameter of the pillar is 0.3~2mm, and the porosity is ≤40%.
[0011] Preferably, the body-centered cubic strut BCCZ is obtained by adding vertical struts to the body-centered cubic BCC.
[0012] Preferably, the method specifically comprises the following steps:
[0013] Step S1: establishing a CAD model of a lattice truss structure through a three-dimensional modeling software and exporting it into an STL format file;
[0014] Step S2: importing the STL format file obtained in step S1 into the selective laser melting equipment, loading FeCoNiAlTi high entropy alloy powder, and adjusting the printing parameters as follows: laser power 140-180 W, scanning speed 800-1400 mm / s, scanning spacing 50 μm, slice layer thickness 30 μm, spot diameter 30-60 μm;
[0015] Step S3: Printing is performed layer by layer along the Z-axis direction under an argon atmosphere to obtain the FeCoNiAlTi high entropy alloy with the lattice truss structure.
[0016] Preferably, the printing parameters in step S2 are: laser power 160 W, scanning speed 1200 mm / s, scanning spacing 50 μm, slice thickness 30 μm, and spot diameter 60 μm.
[0017] Preferably, the oxygen content of the argon atmosphere in step S3 is less than 100 ppm.
[0018] The present invention also provides a FeCoNiAlTi high entropy alloy with a lattice truss structure prepared by the preparation method described in the above technical solution.
[0019] Compared with the prior art, the present invention has the following advantages and technical effects:
[0020] The present invention designs a lattice truss structure according to the rules based on the lattice structure of materials science, and shows high compliance and energy absorption capacity compared with other lattice lattice structures; FeCoNiAlTi high entropy alloy is used as the molding material of the lattice structure, and the alloy is superior to traditional titanium alloys, stainless steel and nickel-based alloys in terms of performance and printing stability. The preparation method provided by the present invention can print out a lattice structure with high microscopic density and excellent performance. The FeCoNiAlTi high entropy alloy with a lattice lattice truss structure prepared by the preparation method provided by the present invention can be used in the fields of vehicles, aerospace and biomedicine, and its lightweight energy absorption characteristics can play a buffering and protective role, further expanding the application range of metal porous materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0022] Figure 1 Schematic diagram of the unit cell of the simple cubic SC in Example 1 and the body-centered cubic BCC in Example 2 of the present invention;
[0023] Figure 2 Schematic diagram of a unit cell of a body-centered cubic pillar BCCZ in Example 3 of the present invention;
[0024] Figure 3 A schematic structural diagram of a FeCoNiAlTi high entropy alloy with a lattice truss structure prepared in Examples 1 to 3 of the present invention;
[0025] Figure 4 Schematic diagram of the process of selective laser melting in Examples 1 to 5 of the present invention;
[0026] Figure 5 A physical picture of the FeCoNiAlTi high entropy alloy with a lattice truss structure prepared in Examples 1 to 3 of the present invention;
[0027] Figure 6 Surface SEM images of FeCoNiAlTi high entropy alloys with lattice truss structures prepared in Examples 1 to 3 of the present invention;
[0028] Figure 7 The internal SEM image of the FeCoNiAlTi high entropy alloy with a lattice truss structure prepared in Example 1 of the present invention;
[0029] Figure 8 Quasi-static compressive stress-strain curve diagram of the FeCoNiAlTi high entropy alloy with a lattice truss structure prepared in Examples 3 to 5 of the present invention;
[0030] Fig. 9 A bar graph showing the yield strength and Young's modulus of the FeCoNiAlTi high entropy alloys with a lattice truss structure prepared in Examples 3 to 5 of the present invention;
[0031] Fig.10 The lattice energy absorption and specific energy absorption bar graphs of the FeCoNiAlTi high entropy alloys with lattice truss structures prepared in Examples 3 to 5 of the present invention. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0034] The embodiment of the present invention provides a method for preparing a FeCoNiAlTi high entropy alloy with a lattice truss structure, comprising the following steps:
[0035] The FeCoNiAlTi high entropy alloy powder is subjected to selective laser melting to obtain a FeCoNiAlTi high entropy alloy with a lattice truss structure;
[0036] The unit cell structure of the lattice truss structure includes a simple cubic SC, a body-centered cubic BCC or a body-centered cubic strut BCCZ.
[0037] In a preferred embodiment, the lattice truss structure is formed by unit cell structures being distributed in an array in three-dimensional directions. The present invention forms a porous structure by expanding the unit cell structure in an array in three-dimensional directions. The structure can be used as a buffer structure inside a vehicle bumper, and its light weight and energy absorption characteristics can play a good protective role.
[0038] In a preferred embodiment, the unit cell structure of the lattice truss structure includes a simple cubic SC, a body-centered cubic BCC or a body-centered cubic strut BCCZ, preferably a body-centered cubic strut BCCZ.
[0039] In a preferred embodiment, the body-centered cubic strut BCCZ is obtained by adding vertical struts to the body-centered cubic BCC. The body-centered cubic strut BCCZ in the present invention exhibits the ability to resist deformation in the direction of force, significantly improving the stiffness and energy absorption capacity of the structure in the direction of force.
[0040] In a preferred embodiment, the size of the unit cell structure is 2mm×2mm×2mm to 10mm×10mm×10mm, more preferably 2mm×2mm×2mm.
[0041] In a preferred embodiment, the pillar diameter of the unit cell structure is 0.3-2 mm; the pillar diameter of the simple cubic SC is 0.6 mm, 0.7 mm or 0.8 mm; the pillar diameter of the body-centered cubic BCC is 0.4 mm, 0.5 mm or 0.56 mm; the pillar diameter of the body-centered cubic pillar BCCZ is 0.36 mm, 0.46 mm or 0.52 mm.
[0042] In a preferred embodiment, the porosity of the unit cell structure is ≤40%.
[0043] In a preferred embodiment, the size of the FeCoNiAlTi high entropy alloy with the lattice truss structure is 12 mm×12 mm×12 mm.
[0044] In a preferred embodiment, the porosity of the FeCoNiAlTi high entropy alloy of the lattice truss structure is calculated by the following formula:
[0045]
[0046] Among them, ρ * is the lattice density, ρ s is the density of solid material, m * is the lattice mass, and V is the lattice discrete volume.
[0047] In a preferred embodiment, the particle size of the FeCoNiAlTi high entropy alloy powder is 15-53 μm; the shape of the FeCoNiAlTi high entropy alloy powder is spherical. The FeCoNiAlTi high entropy alloy powder in the present invention is well spheroidized, has a small amount of satellite particles, has a rough surface, and has a high laser absorption rate.
[0048] In a preferred embodiment, the particle size distribution of the FeCoNiAlTi high entropy alloy powder is: D1019.94%, D5034.75%, D9056.66%.
[0049] In a preferred embodiment, the FeCoNiAlTi high entropy alloy is (FeCoNi) 86 Al7Ti7. The FeCoNiAlTi high entropy alloy used in the present invention is a new type of alloy with high formability in 3D printing, and its printed state has excellent mechanical properties and does not require secondary treatment.
[0050] In a preferred embodiment, the method specifically comprises the following steps:
[0051] Step S1: establishing a CAD model of a lattice truss structure through a three-dimensional modeling software and exporting it into an STL format file;
[0052] Step S2: importing the STL format file obtained in step S1 into the selective laser melting equipment, loading FeCoNiAlTi high entropy alloy powder, and adjusting the printing parameters as follows: laser power 140-180 W, scanning speed 800-1400 mm / s, scanning spacing 50 μm, slice layer thickness 30 μm, spot diameter 30-60 μm;
[0053] Step S3: Under an argon atmosphere, printing is performed layer by layer along the Z-axis direction to obtain a FeCoNiAlTi high entropy alloy with a lattice truss structure.
[0054] In a preferred embodiment, the three-dimensional modeling software in step S1 includes SolidWorks or nTopology.
[0055] In a preferred embodiment, the FeCoNiAlTi high entropy alloy powder in step S2 is produced by a gas atomization method, and has a particle size range of 15 to 53 μm.
[0056] In a preferred embodiment, the printing parameters in step S2 are: laser power 160 W, scanning speed 1200 mm / s, scanning interval 50 μm, slice thickness 30 μm, and spot diameter 60 μm.
[0057] In a preferred embodiment, the oxygen content of the argon atmosphere in step S3 is less than 100 ppm.
[0058] The preparation method of the FeCoNiAlTi high entropy alloy with a lattice truss structure provided by the present invention can realize precise forming of a hollow structure and print out a lattice structure with high microscopic density and excellent performance.
[0059] The present invention also provides a FeCoNiAlTi high entropy alloy with a lattice lattice truss structure prepared by the preparation method described in the above technical solution. The FeCoNiAlTi high entropy alloy with a lattice lattice truss structure provided by the present invention can be used in the fields of vehicles, aerospace, and biomedicine, and its lightweight energy absorption characteristics can play a buffering and protective role, further expanding the application range of porous metal materials.
[0060] The room temperature in the embodiments of the present invention refers to "25±2°C".
[0061] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.
[0062] Example 1
[0063] A preparation method of a FeCoNiAlTi high entropy alloy with a lattice truss structure:
[0064] Step S1: A lattice lattice truss structure model is established by using the modeling software nTopology. The size of the model is 12 mm × 12 mm × 12 mm. The lattice lattice truss structure is formed by a unit cell structure distributed in a three-dimensional array. The generated mathematical model structure is converted into an STL format file. The unit cell structure is a simple cubic SC with a size of 2 mm × 2 mm × 2 mm. The designed pillar diameter is 0.6 mm and the porosity is 20%.
[0065] Step S2: Import the STL format file obtained in step S1 into the 3D printing pre-processing software Magics, set the printing parameters as follows: laser power 160W, scanning speed 1200mm / s, spot diameter 60μm, scanning spacing 50μm, slice thickness 30μm, and obtain the pre-processing file; place the structural model on the software, the model cannot be placed below the platform placement plane, and cannot exceed the printing substrate boundary; import the pre-processing file into the selected area laser melting 3D printer, and produce spherical (FeCoNi) with a particle size of 15 to 53μm by gas atomization 86 Al7Ti7 high entropy alloy powder (the particle size distribution of FeCoNiAlTi high entropy alloy powder is: D1019.94%, D5034.75%, D9056.66%) is placed in a drying oven and kept at 200°C for 3 hours to fully dry, and then the high entropy alloy powder is added to the powder bin of the selective laser melting 3D printer;
[0066] Step S3: In an argon atmosphere with an oxygen content of less than 100 ppm, printing is performed layer by layer along the Z-axis direction. Each layer (FeCoNi) 86 The Al7Ti7 high entropy alloy powder was processed by melting-solidification-remelting mode. The thickness of each powder layer was 30μm and the powder feeding layer thickness was 60μm. After printing, the sample was removed from the substrate by electrospark cutting, and then the sample surface was cleaned with a washing solvent and ultrasonic cleaning to obtain a FeCoNiAlTi high entropy alloy with a lattice truss structure.
[0067] Example 2
[0068] A preparation method of a FeCoNiAlTi high entropy alloy with a lattice truss structure:
[0069] Step S1: A lattice lattice truss structure model is established by using the modeling software nTopology. The size of the model is 12 mm × 12 mm × 12 mm. The lattice lattice truss structure is formed by a unit cell structure distributed in a three-dimensional array. The generated mathematical model structure is converted into an STL format file. The unit cell structure is a body-centered cubic BCC with a size of 2 mm × 2 mm × 2 mm. The designed pillar diameter is 0.4 mm and the porosity is 20%.
[0070] Step S2 and step S3 are the same as in Example 1.
[0071] Example 3
[0072] A preparation method of a FeCoNiAlTi high entropy alloy with a lattice truss structure:
[0073] Step S1: A lattice lattice truss structure model is established by modeling software nTopology, the size of the model is 12 mm × 12 mm × 12 mm, the lattice lattice truss structure is formed by a unit cell structure distributed in a three-dimensional array, and the generated mathematical model structure is converted into an STL format file; wherein the unit cell structure is a body-centered cubic strut BCCZ, which is obtained by adding a vertical strut to the body-centered cubic BCC, the size is 2 mm × 2 mm × 2 mm, the designed strut diameter is 0.36 mm, and the porosity is 20%;
[0074] Step S2 and step S3 are the same as in Example 1.
[0075] Example 4
[0076] The difference from Example 3 is that the diameter of the pillar in step S1 is 0.46 mm, and the remaining steps are the same as Example 3.
[0077] Example 5
[0078] The difference from Example 3 is that the diameter of the pillar in step S1 is 0.52 mm, and the remaining steps are the same as Example 3.
[0079] At room temperature, a CMT-5205 microcomputer-controlled electronic universal testing machine was used to -3 The FeCoNiAlTi high entropy alloys with lattice truss structures prepared in Examples 1 to 3 were subjected to quasi-static uniaxial compression tests at a strain rate of s. The Z-axis direction of the sample was used as the loading direction of the compression test. To ensure the accuracy of the test results, each sample was tested three times. The national standard for metal foam compression test GB / T 31930-2015 was strictly followed from preparation to testing, and the final measured strain rates all exceeded their densification strains.
[0080] Figure 1Schematic diagram of the unit cell of the simple cubic SC in Example 1 and the body-centered cubic BCC in Example 2.
[0081] Figure 2 Schematic diagram of the unit cell of the body-centered cubic pillar BCCZ in Example 3. Figure 2 It can be seen that the body-centered cubic strut BCCZ is obtained by adding vertical struts to the body-centered cubic BCC.
[0082] Figure 3 Schematic diagram of the structure of the FeCoNiAlTi high entropy alloy with a lattice truss structure prepared in Examples 1 to 3.
[0083] Figure 4 Schematic diagram of the process of selective laser melting in Examples 1 to 5.
[0084] Figure 5 The actual image of the FeCoNiAlTi high entropy alloy with lattice truss structure prepared in Examples 1 to 3. Figure 5 It can be seen that the FeCoNiAlTi high entropy alloy with a lattice truss structure prepared by the preparation method provided by the present invention has a complete structure and strong formability.
[0085] The surface of the FeCoNiAlTi high entropy alloys with lattice truss structures prepared in Examples 1 to 3 was observed using a scanning electron microscope. Figure 6 As shown. Figure 6 It can be seen that an obvious printing interface can be observed between the layers of the FeCoNiAlTi high entropy alloy with a lattice truss structure, and no obvious powder hanging phenomenon is observed; in the building direction (XZ plane), it can be seen that a large number of unmelted particles are bonded to its lower part.
[0086] The FeCoNiAlTi high entropy alloy with a lattice truss structure prepared in Example 1 was surface polished and then observed using a scanning electron microscope. The results are as follows: Figure 7 As shown. Figure 7 It can be seen that the internal structure of the FeCoNiAlTi high entropy alloy with a lattice truss structure is uniform and dense, with only a small number of holes and high density.
[0087] The ratio of the actual compressive force applied to the specimen during the experiment to its original cross-sectional area is taken as the compressive stress, and the ratio of the length change in the Z-axis direction to the original height is taken as the compressive strain. The compressive stress-strain curve is drawn. Figure 8 The quasi-static compressive stress-strain curves of the FeCoNiAlTi high entropy alloys with lattice truss structures prepared in Examples 3 to 5, wherein: For Example 3, For Example 4, This is Example 5. Figure 8 It can be seen that there is an obvious compression yield platform for the low-density lattice, while the curve for the high-density lattice tends to change linearly in direct proportion, and there is no obvious plastic collapse inside the lattice structure due to exceeding the plastic deformation capacity.
[0088] Fig. 9 The yield strength and Young's modulus bar graphs of the FeCoNiAlTi high entropy alloys with lattice truss structures prepared in Examples 3 to 5, wherein BCCZ-0.36 is Example 3, BCCZ-0.46 is Example 4, and BCCZ-0.52 is Example 5. Fig. 9 It can be seen that under the same relative density and structure, the yield strength of the traditional lattice structure material Ti6Al4V is 34MPa, which is about 56% higher than the yield strength of the traditional lattice structure material Ti6Al4V. The Young's modulus of BCCZ-0.52 exceeds 2.5GPa, which is close to the stiffness of human bones and can be used for human bionic bones. Therefore, the present invention prepares a lightweight structural material with high strength and stiffness.
[0089] Taking the strain corresponding to the densification stage of the curve as the end point, the area is integrated, and the energy absorption is calculated using Formula 2, and the specific energy absorption is calculated using Formula 3. The results are shown in Fig.10 As shown;
[0090]
[0091]
[0092] Among them, W * is the lattice energy absorption, W m is the specific energy absorption, ε d is the densification strain and ρ is the density of the material in the solid state.
[0093] Fig.10 The lattice energy absorption and specific energy absorption bar graph of the FeCoNiAlTi high entropy alloy with lattice truss structure prepared in Examples 3 to 5 of the present invention. Fig.10 It can be seen that the lattice energy absorption increases with the increase of the pillar diameter (relative density), and the energy absorption exceeds 50MJ / m 3 , exceeding the traditional nickel-based alloy (the maximum energy absorption of nickel-based alloy is less than 10MJ / m 3 ) and medical titanium alloy (the maximum energy absorption of medical titanium alloy is less than 40MJ / m 3 ), etc., showing excellent energy absorption capacity; the specific energy absorption value remains stable, showing the stability of the lattice structure in energy absorption.
[0094] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a FeCoNiAlTi high entropy alloy with a lattice truss structure, characterized in that: The following steps are involved: The FeCoNiAlTi high entropy alloy powder is subjected to selective laser melting to obtain a FeCoNiAlTi high entropy alloy with a lattice truss structure; The unit cell structure of the lattice truss structure is a body-centered cubic strut BCCZ; the body-centered cubic strut BCCZ is obtained by adding vertical struts to the body-centered cubic BCC; the size of the unit cell structure is 2mm×2mm×2mm~10mm×10mm×10mm, the strut diameter is 0.36mm, 0.46mm or 0.52mm, and the porosity is ≤40%.
2. The method for preparing the FeCoNiAlTi high entropy alloy with a lattice truss structure according to claim 1, characterized in that: The FeCoNiAlTi high entropy alloy powder is produced by a gas atomization method, and has a particle size range of 15 to 53 μm.
3. The method for preparing the FeCoNiAlTi high entropy alloy with a lattice truss structure according to claim 1, characterized in that: The specific steps include: Step S1: establishing a CAD model of a lattice truss structure through a three-dimensional modeling software and exporting it into an STL format file; Step S2: importing the STL format file obtained in step S1 into the selective laser melting equipment, loading FeCoNiAlTi high entropy alloy powder, and adjusting the printing parameters as follows: laser power 140-180 W, scanning speed 800-1400 mm / s, scanning spacing 50 μm, slice layer thickness 30 μm, spot diameter 30-60 μm; Step S3: Printing is performed layer by layer along the Z-axis direction under an argon atmosphere to obtain the FeCoNiAlTi high entropy alloy with the lattice truss structure.
4. The method for preparing the FeCoNiAlTi high entropy alloy with a lattice truss structure according to claim 3, characterized in that: The printing parameters in step S2 are: laser power 160 W, scanning speed 1200 mm / s, scanning spacing 50 μm, slice thickness 30 μm, and spot diameter 60 μm.
5. The method for preparing the FeCoNiAlTi high entropy alloy with a lattice truss structure according to claim 3, characterized in that: The oxygen content of the argon atmosphere in step S3 is less than 100 ppm.
6. A FeCoNiAlTi high entropy alloy with a lattice truss structure prepared by the preparation method according to any one of claims 1 to 5.
Citation Information
Patent Citations
High-entropy alloy matrix self-lubrication composite with imitation lattice structure and containing solid lubricant
CN111390166A